Black Dandyism: From Fashion to Freedom - MAASKRI, I Mohamed (My University, 2019)
The act of slavery saw light roughly in 1619, when hundreds of African slaves were shipped to Europe and to the New World to work for the white man. Since then white men have issued laws to keep the slaves in chains. For that reason, black people sought to find a way to express their freedom without breaking those laws. One method was by composing songs, dances and mostly tailing their own fashionable clothes. This movement was called "Black Dandyism" which emerged in England and later swept across Europe and reached America. This historical research aims at first to shed light on how black dandies created a new identity by wearing colorful outfits to reflect their African identity and culture. Second, it explains how the tool of fashion and music became a political movement to impose their culture and existence. Third, the researcher delivers illustrations to demonstrate how Dandyism is portrayed in literature. Finally, it ends on making a link between old Dandyism, the case of Jim Crow, and the modern one with stresses the case of "Michael Jackson."
Keywords: Slavery, Dandyism, African Identity, Fashion, Jim Crow, Michael Jackson.